Chapter 1 The Experimental Turn in Moral and Political Philosophy - Gaitán, Antonio (Taylor & Francis, 2024)
This introduction presents the field of experimental moral and political philosophy as a confluence between different disciplines and research traditions. The chapter begins by highlighting the importance of several historical currents and presenting the scope and nature of a diverse and rich research agenda within the contours of a broad research area. The development of behavioural economics, the revisiting of John Rawls' psychological assumptions in his Theory of Justice, the framework of bounded ethicality, the rebirth of philosophical naturalism, and the burgeoning movement of experimental philosophy are given credit in the convergence leading to the current state of the field. The chapter ends by presenting a few active subfields which, in addition to their social relevance, may strengthen the hybrid enterprise of experimental moral and political philosophy by producing new and interesting results in the coming years.